Jatharagni and Prakriti of young Indian adult population: A descriptive cross-sectional study - Meera Kuttikrishnan; Rudresh Sridhar; Elgeena Varghese (Journal of Ayurveda and Integrative Medicine, 2022)
Agni has an important role to play in the physiological functioning of the body. It varies with the bodily constitution of individuals, season, age, and other factors. The uniqueness of each individual is determined by the Prakriti which deals with somatic and psychic development. The Prakriti directly impacts Jatharagni and determines the type of Jatharagni. A descriptive cross-sectional survey was conducted among healthy students from both genders aged between 18 and 30 years. Jatharagni and Prakriti were evaluated using the Jatharagni Assessment Questionnaire (JAQ) and a 62-item self-assessment questionnaire validated in previous study. The results indicate that there is a significant association between the types of Prakriti and the types of Jatharagni χ2 (6) = 155.14, (p = .001). The post-hoc analysis revealed that Vatapitta is associated with the dominance of Teekshnagni, Vatakapha is associated with the dominance of Mandagni, and Kaphapitta is associated with the dominance of Vishamagni. The result indicates a statistically significant association between types of Prakriti and Jarana Shakthi (Likelihood Ratio (4) = 27.010, p = .001). The study establishes a significant association between Agni and Dvandvaja Prakriti. Vatapitta Prakriti individuals had Teekshnagni, Vatakapha Prakriti individuals had Mandagni and Kaphapitta Prakriti had Vishamagni. Though the results were promising, the analysis should be done with a larger sample size in different populations.